Faktor Faktor yang Berhubungan dengan Hipertensi Pada Lansia di Desa Belang Malum Kabupaten Dairi Tahun 2014 - Susi Napitupulu; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACTHypertension is a degenerative disease that shown the rising of diastole and/or sistoles  blood presur and attack the elder. Hypertension be a health concern because would lead to complications in target organs and make dying World Health Organizatio identified that hypertension as the first causes of cardiovascular mortality 20 until 50% of the mortality.  Hypertension kills nearly 8 million people annually worldwide and nearly 1.5 million people every year in Southeast Asia. Hypertension is associated with several factors, obesity, physical activity, smoking habit, the habit of eating natrium.,and family history.To determine factors associated with hypertension in Desa Belang Malum Kabupaten Dairi tahun in 2014, conducted research using cross sectional design. 100 samples were taken by simple random sampling methodh. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi square test with 95% CI.Based on the results obtained proportion prevalence of hypertension 44,00%, the highest proportion of hypertension respondents is male group (64.86%), workers (45,26%), Academik/College education (75.00%), nutritional status obesity (61.10%), insufficient physical activity (63.63%), the habit of smoking (64.51%), eating salt ≤ 3 time /week (55.26%), and family history (53.33%).The results of  bivariate analyzes, in general there is a significant association between gender (p = 0.001), nutritional status (p = 0.010),  physical activity (p = 0.036), and smoking habit (p = 0.006). And there was no significant relationship between level of education,  the habit of eating natrium, and family history with incident hypertension.The elderly routinely check  the blood pressure , balancereduce the nutritional status by controll the food consumtion or have the sport routinity, add the physical activity by old-age gymnastics, reduce or stop the smooking habit as a risk factor for hypertension. Parties are expected to influence elderly to want  participating in the activities of Posyandu elderly and the worker of Posyandu to held the Health Promotion of the risk of Hypertension, and how the way to prevent the hypertension in elderly.Keywords: Hypertension, Elderly, Risk factors